NILAI-NILAI PENDIDIKAN ISLAM DALAM OBSERVATORIUM - ., Akrim (University of Muhammadiyah Sumatera Utara, 2020)
The observatory is an institution that studies the celestial bodies and is an important legacy of Islamic civilization. In the early development, the observatory focused more on the study of celestial bodies. But in the modern era, observatory institutions have functions and strategic positions in social and intellectual life in the community. Among them the observatory has educational values or aspects. Among the values and functions of education in observatory institutions are: (1) as a means of accusing the times and positions of worship of Muslims (especially prayer and fasting), (2) as a scientific study institution, and (3) as a scientific educational institution.